Emergency beacon for elderly - Soon Woei, Chong (2002)
Emergency Beacon System has become a necessity as the demand for double income families is increasing these days. Due to the limitation of reality, people nowadays are not capable of taking care of the elderly. At the same time, the tremendous increase of cases of sudden death among solitary living elderly had drawn attention to the society to solve this problem. Hence, attaching an emergency beacon system with the elderly will guarantee the safety of the elderly where immediate assistance will be provided when the system is activated. Currently, several types of cell phones in the market attempted to provide solution to this problem by including emergency beacon function such as speed dialing. However, these beacons are using voice based emergency system and is not efficient due to the nature where human will feel panic or blank out their mind when emergency occurs and resulting in difficulties in providing correct information when something emergency occurred. Besides that, it is difficult for elderly with vision problem to press the speed dial button if depending on cell phone. These issues might delay the rescue time and cause some avoidable tragedies. These limitations become a motivation to develop an easy to operate, low cost, SMS based and user friendly emergency beacon system. The purpose of this microcontroller-based emergency beacon system is to send multiple text messages to certain preset numbers by activating a push button via GSM network. Color coded dedicated push button make it easy for elderly to send emergency message. An alarm function will remind elderly to update their current status for their family or guardian. Necessary information will preset into the system and sent out automatically to resolve the issues of blank out during emergency. For further enhancement, this system can be integrated using a GPS module to detect the current location and it will become a perfect emergency beacon system which can be used in any place to trace the location of the sender to provide necessary assistance immediately.